2017
DOI: 10.1111/cdev.12690
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Targeted School Violence by Responding to Students' Psychosocial Crises: The NETWASS Program

Abstract: The standardized, indicated school-based prevention program "Networks Against School Shootings" combines a threat assessment approach with a general model of prevention of emergency situations in schools through early intervention in student psychosocial crises and training teachers to recognize warning signs of targeted school violence. An evaluation study in 98 German schools with 3,473 school staff participants (M age = 46.2 years) used a quasi-experimental comparison group design with three measurement poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…Without doubt it will be a central task of future research to test this hypothesis against a reliable database and it will be a central topic for future development activities in the domain of preventive interventions (cf. Cornell & Scheithauer, 2011; Leuschner et al, 2017). …”
Section: Limitations and Outlookmentioning
confidence: 99%
“…Without doubt it will be a central task of future research to test this hypothesis against a reliable database and it will be a central topic for future development activities in the domain of preventive interventions (cf. Cornell & Scheithauer, 2011; Leuschner et al, 2017). …”
Section: Limitations and Outlookmentioning
confidence: 99%
“…The NETWASS program aims to prevent severe, targeted school violence through the combination of a structured threat assessment approach based on the Virginia Student Threat Assessment Guidelines (Cornell, 2013;Cornell & Sheras, 2006) with a developmentally-informed model for early and indicated crisis prevention (Leuschner et al, 2011;2017;Scheithauer, Leuschner, & NETWASS Research Group, 2014). Case analyses have shown that school shootings were long-term planned, targeted attacks and resulted from an individual psychosocial crisis of the perpetrators (O'Toole, 1999;Verlinden, Hersen, & Thomas, 2000;Vossekuil, Fein, Reddy, Borum, & Modzeleski, 2002;cf.…”
Section: The Network Against School Shootings (Netwass) Programmentioning
confidence: 99%
“…Since intervention programs are increasingly expected to be evidence-based and specify the active ingredients, "black box"-outcome studies are recognized as insufficient to establish a program's effectiveness (Leuschner et al, 2017;Mowbray et al 2003). While some evaluators have articulated and validated the core components of their programs (Chamberlain, 2003;Forgatch, Patterson, & Degarmo, 2005;Henggeler, Schoenwald, Liao, Letourneau, & Edwards, 2002;Webster-Stratton & Herman, 2010), few authors provide sufficient guidance about the critical features of their programs (Dane & Schneider, 1998;Durlak & DuPre, 2008;Gould et al, 2016).…”
mentioning
confidence: 99%
“…Thus, there is much evidence that experiences of victimization, humiliation, and exposure to violence in childhood and adolescence are powerful predictors of subsequent crisis and violence, all too often creating vicious cycles of bullying, rejection, violence, and aggression (Averdijk, Malti, Eisner, Ribeaud, & Farrington, ; Salmivalli, ; see Leuschner et al., ; Yablon, ).…”
Section: Detection Of Syv Riskmentioning
confidence: 99%
“…An example of a promising approach to prevent SYV is presented in the last article of our special section by Leuschner et al. (). This article introduces the results of a large‐scale quasi‐experimental evaluation of an evidence‐based prevention program that combines a threat assessment approach with a general model to prevent crisis situations in schools.…”
Section: Prevention and Intervention Of Syvmentioning
confidence: 99%